Analisis Nilai Tambah Usaha Pengolahan Ubi Kayu Menjadi Getuk Rol Pelangi Di Desa Saptorenggo Kecamatan Bahuga Kabupaten Way Kanan Lampung - Aisah (Jurnal Bakti Agribisnis, 2022)
Fresh cassava has a very low economic value at the time of harvest, therefore an effort is needed to increase the added value of cassava by processing it into a variety of products. With the existence of food diversification, it is suggested that traditional wisdom needs to be explored in utilizing food ingredients that come from outside rice. There are many types of processed food made from cassava that are liked by the community, one of which is getuk. Saptorenggo Village is one of the villages in Bahuga Subdistrict, Way Kanan Regency, where the majority of the population has a livelihood as farmers. In the village there is a home industry that processes cassava into processed food called Getuk Roll Pelangi. The home industry for the rainbow roll getuk processing is an effort to increase the added value of cassava, where at the time of harvest the selling price is low and cannot increase more income for farmers. By processing this cassava into rainbow roll food, it can increase the durability of cassava and the selling value of cassava is higher so that it can increase family income. The objectives are: 1). To know the business income of processing cassava into rainbow roll getuk in Saptorenggo Village, Bahuga District, Way Kanan Regency. 2) Knowing the added value obtained from the business of processing cassava into rainbow roll getuk in Saptorenggo Village, Bahuga District, Way Kanan Regency. 3) Analyzing the financial feasibility of processing cassava into rainbow roll getuk in Saptorenggo Village, Bahuga District, Way Kanan Regency. The results showed that the production cost of the rainbow roll getuk processing business in Saptorenggo Village, Bahuga District, Way Kanan Regency in one production process was Rp. 205,600, revenue was Rp. 300,000 and income was Rp. 94,400. The value of the R/C ratio is 1.46. The added value of the business of processing cassava into rainbow roll getuk in Saptorenggo Village, Bahuga Subdistrict, Way Kanan Regency is Rp. 169,400/Process or Rp. 5,600 per package of rainbow roll getuk or Rp. 14,100 per Kg of cassava.